Spatially Continuous Modeling and Control of Swing Dynamics in Electric Power Grids*. Issue 1 (July 2017) - Sirota, Lea; Annaswamy, Anuradha M.
Abstract: We propose a new control approach for swing oscillation suppression in large power grids, based on a spatially continuous representation of the system. Traditional modeling is spatially discrete irrespective of the grid size, perceiving the swing dynamics as frequency and phase oscillations. However, we show that for long chains of generators the overall swing dynamics is essentially governed by propagating electro-mechanical waves, retrieving the oscillations only locally. We therefore model the system by partial differential equations, where we decompose the grid into open and closed ended chains of generators, strings and rings. The key principle of the proposed approach is generation of unidirectional control waves that achieve closed loop matching of measured disturbance waves. While in strings this is naturally implemented by actuation at the boundary, the lack of boundaries in rings poses significant challenges. We solve the problem by introducing a new method for interior generation of near exact uni-directional waves. The method, which we denote by Interior Wave Suppression control, requires a minimal number of concentrated actuation and measurement devices for a given ring.